2019
DOI: 10.1111/mcn.12833
|View full text |Cite
|
Sign up to set email alerts
|

In‐depth assessment of snacking behaviour in unmarried adolescent girls 16–19 years of age living in urban centres of Java, Indonesia

Abstract: Adolescence is a critical period characterized by physical, social, and developmental changes that impact on health and eating behaviour. Indonesia is experiencing dramatic economic and infrastructural changes, causing greater access to the global food industry and media. This transition is influencing food intake trends, leading to new nutritional challenges in adolescent girls. Qualitative research was conducted between November 2016 and January 2017 in five urban sites in Java, Indonesia, to examine individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 33 publications
1
60
1
2
Order By: Relevance
“…The full‐text review resulted in a total of 72 included references 56‐127 reporting on a total of 71 studies from 27 different countries, with 23 studies conducted in Africa, 34 in Asia, and 14 in South America. Figure 1 shows details of references screened, included and excluded, and Table 1 shows the general characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The full‐text review resulted in a total of 72 included references 56‐127 reporting on a total of 71 studies from 27 different countries, with 23 studies conducted in Africa, 34 in Asia, and 14 in South America. Figure 1 shows details of references screened, included and excluded, and Table 1 shows the general characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Availability and affordability are also particularly relevant to adolescents with agency to buy snacks for themselves on the way to and from school. For instance, adolescent girls in Indonesia explained during in-depth interviews how the wide availability of affordable and 'tasty' snacks made them appealing (Blum et al, 2019). Focus group discussions and interviews with 8-11-year-olds in Kenya indicated excess consumption of fast foods and sweetened beverages was due to the availability of cheap snacks in the environment surrounding the school (Kigaru et al, 2015).…”
Section: Step 3 Assess the Reasons Why Children Are Or Are Not Eatmentioning
confidence: 99%
“…Secondly, diet with lower GI/GL can be recommended to healthy individuals as a convenient alternative for a proportionate serving of a higher GI/GL snack bar; and can be considered as a reliable source of high-quality protein, fiber, and other nutrients, which may help with blood glucose regulation. This is important because unhealthy snacking is reported to be pervasive in Indonesia as well as among adolescent girls (Blum et al 2019). Within the study, it was reported that adolescent girls snack multiple times daily on foods high in sugar, salt, and fat (Blum et al 2019).…”
Section: Glycaemic Responsementioning
confidence: 95%
“…This is important because unhealthy snacking is reported to be pervasive in Indonesia as well as among adolescent girls (Blum et al 2019). Within the study, it was reported that adolescent girls snack multiple times daily on foods high in sugar, salt, and fat (Blum et al 2019).…”
Section: Glycaemic Responsementioning
confidence: 95%